The Elizabethan Theatre and "The Book of Sir Thomas More'' - McMillin, Scott (Cornell University Press, 2019)
The manuscript of the Elizabethan play Sir Thomas More has intrigued scholars for over a century because three of its pages may have been written by Shakespeare. The Elizabethan Theatre and "The Book of Sir Thomas More" sets aside the timeworn question of authorship and considers the play in a new framework, one which by focusing on questions of the theatre attempts to free Elizabethan theatre history from the grip of its most famous author. Bringing to bear on the manuscript the perspective of a theatre historian and the resources of textual scholarship, Scott McMillin departs from most critical accounts, which have judged Sir Thomas More unfinished. Rather, McMillin addresses the manuscript as a coherent and finished work that achieves its intended purpose: to serve as a prompt book in the Elizabethan playhouse. His systematic analysis of the Sir Thomas More manuscript shows that the company for which it was written was unusually large, that it had a lead actor of outstanding capability, and that in its staging of the play it probably made use of visual repetition as an ironic device. He concludes that the theatre company of the period that most closely matched this description was Lord Strange's men, a company, incidentally, for which Shakespeare himself was known to have written in the early 1590s.Textual scholars, theatre historians, and students and scholars of Elizabethan drama will welcome The Elizabethan Theatre and "The Book of Sir Thomas More."
Keywords: Shakespeare, William, -- 1564-1616 -- Authorship.; More, Thomas, -- Saint, -- 1478-1535 -- In literature.; Sir Thomas More (Drama); More, Thomas, -- Saint, -- 1478-1535; Shakespeare, William, -- 1564-1616; Theater -- England -- History -- 16th century.; Performing Arts & Drama.; West European History.; Théâtre -- Angleterre -- Histoire -- 16e siècle.; PERFORMING ARTS / Theater / History & Criticism.; Authorship; Literature; Theater; England; 1500-1599; Electronic books.; History